Advantages and disadvantages of societal engagement: a case study in a research and technology organization. Issue 3 (1st September 2020) - Steen, Marc; Nauta, Joram
ABSTRACT: We view Societal Engagement (SE) as a key element of Responsible Innovation (RI) and want to better understand the advantages and disadvantage of SE, both in theory and in practice. Moreover, we are interested in the role that Research and Technology Organizations (RTOs) might play in bridging the gap between fundamental research in academia and applied research, development and deployment. We reviewed relevant literature in order to identify and discuss the potential advantages and disadvantages of SE, and conducted a case study of one SE initiative within a RTO in order to understand the advantages and disadvantages of SE in practice . The paper closes with a discussion of responsibility and ethics that the organizing of SE would require.